Etoposide-induced DNA damage in a chromosomal breakpoint of RUNX1 gene is independent of RUNX1 expression. (2019) - Schnake, Nicolás; Gutiérrez, Soraya
Abstract: In this work, we analyzed the association between RUNX1 gene expression and the accessibility of BCR3, one of RUNX1 gene breakpoint regions involved in the chromosomal translocation (8;21), a frequent translocation in treatment-related acute myeloid leukemia patients. To this end, we evaluate DNA damage generation induced by in vitro etoposide treatment of KG-1 and Colo320 cells. Our results show that treatment using clinical doses of etoposide for 24 h induces the generation of DNA double strand breaks in the BCR3 of RUNX1 gene in KG-1 cells, but not in Colo320 cells, even though both cell lines express RUNX1 gene. These findings suggest that chromatin accessibility and DNA damage generation at the BCR3 due to treatment with etoposide, is independent of RUNX1 gene expression.